Direct Instruction in very remote schools: a rejoinder to Guenther and Osborne (2020). Issue 2 (14th December 2020) - Buckingham, Jennifer
Abstract: In an article published in this journal, Guenther and Osborne (2020) use data from the reading test of the National Assessment Program for Literacy and Numeracy (NAPLAN) to evaluate the effectiveness of the Flexible Literacy for Remote Primary Schools program in its first 3 years of implementation. However, their analysis has some serious flaws, including that the 'post-intervention' data were actually collected from the start of the implementation period. This calls their conclusions that the program was ineffective into question.